2019
DOI: 10.1016/j.icarus.2018.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Meteoritic abundances of fatty acids and potential reaction pathways in planetesimals

Abstract: The origin of fatty acids on the prebiotic Earth is important as they likely formed the encapsulating membranes of the first protocells. Carbon-rich meteorites (i.e., carbonaceous chondrites) such as Murchison and Tagish Lake are well known to contain these molecules, and their delivery to the early planet by intense early meteorite bombardments constitutes a key prebiotic source. We collect the fatty acid abundances measured in various carbonaceous chondrites from the literature and analyze them for patterns … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 87 publications
1
31
0
Order By: Relevance
“…The frozen ribose might have been preserved until it was distributed in the solar system as fragments of the parent body, and some of the fragments fell to the Earth as meteorites. Extraterrestrial organic and prebiotic molecules were found in meteorites on the Earth’s surface today, see, e.g., [ 1 , 40 , 110 , 111 , 112 , 113 , 114 ], although the possibility of at least partial terrestrial contamination has to be considered. Theoretical studies coupled with experimental data [ 2 , 3 , 115 , 116 ] suggested that a significant portion of organics might survive the heating due to friction in the atmosphere and the energy of the impact [ 117 ] and arrive intact on the Earth’s surface even in comets and interplanetary dust particles.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen ribose might have been preserved until it was distributed in the solar system as fragments of the parent body, and some of the fragments fell to the Earth as meteorites. Extraterrestrial organic and prebiotic molecules were found in meteorites on the Earth’s surface today, see, e.g., [ 1 , 40 , 110 , 111 , 112 , 113 , 114 ], although the possibility of at least partial terrestrial contamination has to be considered. Theoretical studies coupled with experimental data [ 2 , 3 , 115 , 116 ] suggested that a significant portion of organics might survive the heating due to friction in the atmosphere and the energy of the impact [ 117 ] and arrive intact on the Earth’s surface even in comets and interplanetary dust particles.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that over time, many individual carbonaceous chondrites landed in natural ponds rather than on bare land [ 40 ]. These provided the starting constituents, including a variety of amino acids [ 28 , 149 ] and membrane-forming amphiphiles [ 15 , 150 ]. An advantage of this proposal is that it is amenable to laboratory analysis because of the availability of the meteoritic starting material.…”
Section: Comparison With Other Macrobiontsmentioning
confidence: 99%
“…McCollom 2013;Milesi et al 2015;Dalai et al 2016;Steele et al 2018;Franz et al 2020). Taken together, these various sources would have provided, inter alia, polyaromatic hydrocarbons, alkanes, amines, fatty acids/lipids, carboxylic acids, amino acids, nucleobases, aldehydes, ketones and carbohydrates, all of which are presentalong with marked enantiomeric excessesin carbonaceous chondrites (Botta and Bada 2002;Simoneit 2004;Myrgorodska et al 2015;Dalai et al 2016;Furukawa et al 2019;Lai et al 2019).…”
Section: Abiotic Organic Matter: Molecular Pseudofossilsmentioning
confidence: 99%